PENGARUH UMUR PINDAH TANAM BIBIT DAN APLIKASI BAKTERI FOTOSINTESA PADA SISTEM HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL PAKCOY (Brassica rapa L.) - Baskoro, Ardika Cahyo; Nurhayati, Dewi Ratna; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2024)
The focus of the research was to find and analyze the interaction between the effect of transplanting age of seedlings and the application of photosynthetic bacteria on the growth and yield of pak choy (Brassica rapa L.). This research activity was carried out at the ARD Farm Garden from December 2023 to January 2024. Factorial experiment (4 x 3) with a total of 3 repetitions in the research. The first factor is the treatment of transplanting age (S), namely: S0: age 10 DAS, S1: age 13 DAS, S2: age 16 DAS. The second factor is the treatment of folier application of photosynthetic bacteria 2ml/liter (F), namely: F0: control application, F1: folier application 3 DAT, F2: folier application 7 DAT, F3: folier application 10 DAT. Analysis of variance (ANOVA) was used to analyze the data statistically before carrying out further tests using the Honestly Significant Difference (BNJ) at the 5% level. The research parameters observed included; number of leaves, leaf width, crown weight, and harvest index. The research results showed that the best growth of pak choy was in the transplanting treatment at 16 DAS with folier application at 7 DAT. The research results showed that the best pak choy harvest was in the transplanting treatment at 16 DAS and folier application at 10 DAT.